Glyphosate analysis in water samples by luminescence spectroscopy using lanthanides as chromophores - Faria, Talita Nunes de [UNIFESP] (2022)
The development of techniques seeking glyphosate’s analysis by analytical methods has been broadly studied for the past years. However, many methods still require expensive resources, making them not so practical. Thus, the present project will embrace quantitative glyphosate analysis in water samples by luminescence and UV-Vis absorption spectroscopy, using lanthanides complexes as chromophores. The goal is to develop a method for glyphosate quantification using lanthanides complexes, Eu(DPA)3 e Tb(DPA)3. As result, the method achieved plentiful its goal regarding glyphosate analysis, but it still needs to have its maximum and minimum limits of detection studied. Also, the method needs to be aggregated with other procedures to minimize disturbances caused by interferents. With the method was possible to analyze glyphosate concentrations based on Brazilian regulations. The developed method had its result compared to a well stablished HPLC methodology, and the absolute error was 2 ppm. Furthermore, with HPLC was also possible to verify the intermediate compounds are formed while glyphosate concentration increases with the same complex concentration. Finally, interferent analysis was done considering maximum limit of some common ions present in potable water, according to Brazilian legislation. As a result, the presence of certain ions, as ferric and cupric, decrease lanthanides emission.